Plasticidade fisiológica, comportamental e morfológica de Brevicoryne brassicae (L. 1758) (Hemiptera: aphididae) na utilização de distintos hospedeiros - Pereira, Cristiane Dias (2001)
Aphids can respond to the attack of natural enemies with adaptative changes on its morphology, behavior and life cycle. The objective of this work was to verify the differentiate formation of winged morphs, produced in colonies of the aphid Brevicoryne brassicae after exposition to the parasitoid Diaretiella rapae. Experimental colonies (n=14) were initiated transferring ten adult aphids to isolated cabbage plants inside transparent recipients. When the colonies had reached about 56 individuals, a parasitoid couple was placed inside each recipient-test, and they are allowed to oviposited freely for three hours. The Mann-Whitney test was used to verify if the production of winged was the same in the control and in the treatment, The Pearson correlation index was calculated between the number of winged individuals and the number of mummies formed. Medium values were calculated for number of winged morphs, number of mummies, longevity of the parasitoid and number of males and females that emerged, winged morphs were formed earlier in the treatments (7,6+-1,2 days) than in the controls (24+-3,0 days). The Mann-Whitney test indicated that there was significant difference in the number of winged individuals formed between treatment and control (U=48; P<0.002). Significant correlation was not veriﬁed between the number of winged individuals and number of mummies (r=0.69; P=0.90). Eighty one mummies were formed, but only 62.9% had successfully emerged (66.6% males and 33.4% females). The longevity was 2,3+-0,2 days and the parasitoidism percentage varied among the treatments (20,6+-5.2). The clone of B. brassicae answered to the presence of the parasitoid D. rapae increasing the production of winged morphs in laboratory condition. This can be considered a defense mechanism, whereas aphids could strategically maintain the clone survivorship, escaping by flight to form a new colony in other hosts.